2012
DOI: 10.5402/2012/585496
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Fluid Dynamic and Heat Transfer in a Compact Heat Exchanger Using Nanofluids

Abstract: Compact heat exchangers (CHEs) are characterized by a high surface area per unit volume, which can result in a higher efficiency than conventional heat exchangers. They are widely used in various applications in thermal fluid systems including automotive thermal fluid systems such as radiators for engine cooling systems. Recent development of nanotechnology brings out a new heat transfer coolant called "nanofluids," which exhibit larger thermal properties than conventional coolants due to the presence of suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…where ρ c ,T c , C c , v, and k c represent the mass density, temperature, heat capacity, velocity, and thermal conductivity of the coolant (water), respectively. The continuity equation [29] for the coolant is expressed as below…”
Section: Governing Equations and Numerical Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…where ρ c ,T c , C c , v, and k c represent the mass density, temperature, heat capacity, velocity, and thermal conductivity of the coolant (water), respectively. The continuity equation [29] for the coolant is expressed as below…”
Section: Governing Equations and Numerical Simulationmentioning
confidence: 99%
“…Most of the research studies covered the design aspects of cooling systems, focusing toward optimizing the cooling path design and contact area involved in heat transfer. Gunnasegaran et al [ 29 ] showed that a rectangular‐shaped microchannel (MC) with a smaller hydraulic radius is more effective compared to the trapezoidal and triangular channels because of its lower friction factor and pressure loss. It is noteworthy to mention that the coolant pressure drop affects the energy consumption of the coolant pump used in cooling systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, engineers come out with one wonderful solution, at which one revolution device has been developed decades ago called compact heat exchanger (CHE). Hence, Compact heat exchangers are capable to transfer further energy in a very limited cost method than other types of heat exchangers with more energy-saving when compared to conventional technology [19,[28][29]. This study enclosed the examination, imitation, and the investigation of modifications in geometrical factors modifications of louvered fin compact heat exchanger, CHE.…”
Section: Compact Heat Exchenger 71 Compact Heat Exchanger With Louvered Finsmentioning
confidence: 99%
“…CHEs are characterized by a high surface area per unit volume, which can result in a higher efficiency than conventional heat exchangers. Hence, CHEs are able to transfer more energy in a cost-effective manner than other types of heat exchangers and enable more energy saving when compared to standard technology [1][2][3]. CHEs have been widely used in automotive thermal fluid systems such as radiators or air coolers for engine cooling systems and as intercoolers in turbocharging systems.…”
Section: Introductionmentioning
confidence: 99%